Necessidade de informação por parte de gerentes e técnicos: um estudo comparativo - Cassandra Guimaraes de Freitas (1994)
The study compares information needs of managers and their sobordinates in the metalurgy industry in the State of Minas Gerais, Brazil, External and internal information sources were assessed in terms of their importance, frequency of acess, reability and volume of information transmited. The tests of hypotheses led to the conclusion that among other factors, managers are more involved in information seach than nomanagerial professionals.